2020
DOI: 10.3892/etm.2020.8503
|View full text |Cite
|
Sign up to set email alerts
|

Successful total hip arthroplasty for autosomal dominant osteopetrosis complicated by hip osteoarthritis: A case report and review of the literature

Abstract: Osteopetrosis is a rare congenital bone disorder, characterized by systemic osteosclerosis due to a deficiency of or functional defect in osteoclasts. Autosomal dominant osteopetrosis (ADOP) is the most common form with a late onset, a stable condition, relatively few symptoms and a good prognosis. Few studies to date have reported successful total hip arthroplasty (THA) in patients with ADOP and its operative difficulties. We herein describe a case of left hip osteoarthritis in a patient with OP via THA in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In the present case, there were no adverse events during the postoperative rehabilitation course, both in affected and non-affected regions. These results imply the safety of a standard rehabilitation and reinforce the suggestion by Gao et al [ 10 ]. They reported a case of a 52-year-old female patient with osteopetrosis who was able to walk with sticks 18 days after THA and stated that postoperative functional exercises for patients with osteopetrosis ought to be carried out “as usual.”…”
Section: Discussionsupporting
confidence: 91%
“…In the present case, there were no adverse events during the postoperative rehabilitation course, both in affected and non-affected regions. These results imply the safety of a standard rehabilitation and reinforce the suggestion by Gao et al [ 10 ]. They reported a case of a 52-year-old female patient with osteopetrosis who was able to walk with sticks 18 days after THA and stated that postoperative functional exercises for patients with osteopetrosis ought to be carried out “as usual.”…”
Section: Discussionsupporting
confidence: 91%
“…Some have concluded that total hip arthroplasty is a safe and effective procedure for use in patients with osteopetrosis if there is careful preoperative planning. 9 In the present case, we accurately measured the patient’s bone density, her degree of medullary stenosis, and the difference in length between her two lower extremities by means of complete preoperative imaging to more fully assess the brittleness of the bone, the difficulty of marrow expansion and the complexity of repositioning. Such patients have high bone density and extremely brittle bones, which greatly increases the risks of intraoperative fracture and saw blade breakage.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…The investigators strongly recommended that surgeons prepare small dilation tools and small prostheses prior to such procedures to cope with the narrow medullary cavities and high risk of femoral fractures. 9 Individualized femoral stem prostheses and intramedullary guidance systems have also been used for hip replacement in patients with osteopetrosis, 11 but the biggest drawback of customized prostheses is their high cost.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…For patients with life-threatening diseases only, HSCT is still a risky procedure with many potential side effects. The application of the procedure was expanded to include autoimmune diseases as its rate of success has risen [7,8] including malignant infantile osteoporosis and inherited skeletal dysplasia [9,10]. Conjunction with mucopolysaccharidosis [11].…”
Section: Introductionmentioning
confidence: 99%